Growth of mixed and intact litters compared - Koch, B.A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Mixing litters after weaning did not significantly affect rate of gain or efficiency of growing pigs. Weight gains were similar (1.57 or 1.49) for mixed litters and intact litters during a 28-day post-weaning trial.
Swine Industry Day 1970 is known as Swine Day, 1970
Keywords: Swine; Growth; Mixed vs. intact litters